2021
DOI: 10.1080/19424280.2021.1892834
|View full text |Cite
|
Sign up to set email alerts
|

Effects of running in minimal, maximal and traditional running shoes: a musculoskeletal simulation exploration using statistical parametric mapping and Bayesian analyses

Abstract: The current study aimed to use a musculoskeletal simulation approach to examine running biomechanics in minimal, maximal and traditional running shoes using a concurrent SPM and Bayesian approach. Thirteen male participants ran over a force platform at 4.0 m/s in minimal maximal and traditional running shoes. Lower extremity joint loading and muscle forces were explored using a musculoskeletal simulation approach. Differences between conditions were examined using statistical parametric mapping (SPM) and Bayes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 54 publications
(76 reference statements)
2
12
1
Order By: Relevance
“…Kinetic metrics relevant to the hamstrings were identified in 88 studies, 10 reporting on hamstring muscle‐based kinetics, and 83 on joint‐based kinetics to which the hamstrings may contribute. Run speeds captured ranged from 4.0 m/s in many included studies ( n = 30), 33,36,44–70 up to 10.0 ± 0.3 m/s 71…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetic metrics relevant to the hamstrings were identified in 88 studies, 10 reporting on hamstring muscle‐based kinetics, and 83 on joint‐based kinetics to which the hamstrings may contribute. Run speeds captured ranged from 4.0 m/s in many included studies ( n = 30), 33,36,44–70 up to 10.0 ± 0.3 m/s 71…”
Section: Resultsmentioning
confidence: 99%
“…Run speeds captured ranged from 4.0 m/s in many included studies (n = 30), 33,36, up to 10.0 ± 0.3 m/s. 71 Muscle kinetics data were extracted for semitendinosus (ST) (n = 5), 12,46,64,65,72 semimembranosus (SM) (n = 4), 12,64,65,72 biceps femoris (BF) (n = 1), 72 biceps femoris short head (BFsh) (n = 3), 12,64,65 biceps femoris long head (BFlh) (n = 4), 12,46,64,65 and the collective hamstring muscle group (HAMS) (n = 5). [73][74][75][76][77] The metrics extracted were muscle force (n = 8), 12,46,64,65,72,73,76,77 muscle power (n = 2), 12,76 muscle work (n = 4), 12,72,73,76 percentage of muscle simulated maximum (n = 1), 46 and contribution to hip extension/knee flexion internal moment (n = 1) 77 (Appendix S4).…”
Section: Electromyographic Studiesmentioning
confidence: 99%
“…Previous research has reported that walking and running in flat, flexible footwear increase the peak ankle plantarflexor moment and power compared with traditional cushioned shoes (41)(42)(43). It is proposed that this increase in ankle joint kinetics may increase the risk of injury to the ankle plantarflexor musculature and Achilles tendon (42).…”
Section: Discussionmentioning
confidence: 99%
“…For inclusion in this investigation, participants were required to complete a minimum of 35 km per week of training and be between the ages of 18 and 40. Using data from our previous work [27] with a mean ± SD difference in peak compressive ankle joint contact force of 0.69 ± 0.76 BW between conditions, it was determined that in order to achieve 80% power (β) for a p-value of 0.05 (α), 15 runners would be required for a within-subjects comparison between footwear. All participants were free from pathology at the time of data collection and provided written informed consent in accordance with the principles outlined in the Declaration of Helsinki.…”
Section: Participantsmentioning
confidence: 99%
“…The footwear used during this study consisted of New Balance, 1260 v2 (New Balance, Boston, Massachusetts, United States; termed conventional running shoes); Vibram Five-Fingers, ELX (Vibram, Albizzate, Italy; termed minimal); and HOKA OneOne Rapa Nui 2 Tarmac Road (HOKA Goleta, California, United States; termed maximal) (Figure 1a-c). The footwear were scored using the minimalist index of Esculier et al [20], and their details are shown in Using data from our previous work [27] with a mean ± SD difference in peak compressive ankle joint contact force of 0.69 ± 0.76 BW between conditions, it was determined that in order to achieve 80% power (β) for a p-value of 0.05 (α), 15 runners would be required for a within-subjects comparison between footwear. All participants were free from pathology at the time of data collection and provided written informed consent in accordance with the principles outlined in the Declaration of Helsinki.…”
Section: Footwearmentioning
confidence: 99%